P4_6 Shoot for the Moon - Sainty, William; Graham, Holly; Kneeshaw, Sam; Howard-Clark, Simon (Physics Special Topics, 2017)
In this paper we calculated the maximum mass that could be red from a 32 MJ railgun to strike the surface of the Moon to be 0.52 kg, assuming an airless Earth. The muzzle velocity of the projectile was found to be 11.1 kms-1and the speed at which it would hit the surface of the moon is 1.90 kms^-1.